دور الإعلام المرئي في مواجهة الإساءة للرسول صلى الله عليه وسلم . - ميلودي, أماني; سالمي, مروة (University of eloued جامعة الوادي, 2021)
"ملخص الدراسة : تناولت الدراسة "" دور الإعلام المرئي في مواجهة الإساءة للرسول صلى الله عليه وسلم عبر دراسة ميدانية على عينة من اعلاميي ولاية الوادي "". واعتمدت هذه الدراسة على المنهج الوصفي المسحي بطريقة قصدية متاحة متكونة من 52 اعلامياً. وإن من أهم النتائج التي خلصت إليها هذه الدراسة : 1.تواجه الأمة الإسلامية هجمات من الدول الغير مسلمة ، وتصويرهم للإسلام بأبشع الصور عبر وسائلهم الإعلامية . 2.تستخدم وسائل الإعلام حملات واعلانات للدفاع عن الرسول صلى الله عليه وسلم . 3.للإعلام المرئي دور بارز في نشر الدعوة الإسلامية وإظهار الدين الحق فبذلك عليه أن يقوم بعمل برامج لنصرة النبي المصطفى صلى الله عليه وسلم. 4.إن الرسول صلى الله عليه وسلم مرسل من الله إلى الناس كافة مبشراً ومنذرا وهاذياً للخير وسراجاً منيراً فلذلك فإن نصرته والدفاع عنه أمر عظيم وعلامة من علامات الإيمان . 5.ونظراً لقلة الإعلاميين و الصحفيين في الولاية خاصة فئة المراسلين فإننا وجدنا صعوبة في الحصول على أكبر عدد من الإجابات على الإستبيان."Summary of the study.: The study dealt with ""the role of visual media in the face of abuse of the Prophet (peace be upon him) through a field study on a sample of the media of the valley state."" This study relied on the descriptive survey method in a deliberate manner available consisting of 52 media professionals. One of the most important findings of this study is : 1. The Islamic nation is facing attacks from non-Muslim countries, and their depiction of Islam in the most horrible way through their media. 2. The media use loads and advertisements to defend the Prophet. 3. The visual media has a prominent role in spreading the Islamic da'wa and demonstrating religion , so he has to make programs to support the Prophet Mustafa ( peace be upon him). 4. The Prophet (peace be upon him) is sent from God to all people as a missionary, an atom, a good lord anda enlightened secret, so his victory and defense is great and a sign of faith. 5. Given the lack of media professionals and journalists in the state, particularly the correspondent category, we found it difficult to get as many answers as possible to the questionnaire "
دعوة
Keywords: " الإساءة ، المواجهة ، الإعلام المرئي.محمد صلى الله عليه وسلم "; Abuse, confrontation, visual media.muhamad salaa allah ealayh wasalam